Reliability and validity of the Thai version of the 2007 revised Developmental Coordination Disorder Questionnaire - Nantiwat, Natewimon; Sutchritpongsa, Sureelak; Penphattarakul, Amornrat; Wannapaschaiyong, Prakasit; Ketudat, Nattha; Rojmahamongkol, Pat (Journal of Associated Medical Sciences, 2025)
Background: Developmental coordination disorder (DCD) manifests with clumsiness and affects children’s daily activities, academic achievement, peer acceptance, and self-esteem. Early identification and intervention are crucial for improving quality of life. There is no screening test for DCD in Thailand. The 2007 revised version of the Developmental Coordination Disorder Questionnaire (DCDQ’07) is a caregiver-report screening test for 5 to 15-year-old children globally used with good sensitivity and specificity. Objectives: To translate and validate the Thai version of the DCDQ’07 (DCDQ-T), assessing its content validity, internal consistency, test-retest reliability, and inter-rater reliability. Materials and methods: After receiving permission from the original questionnaire developer, forward and backward translation processes were performed. The content validity index (CVI), consisting of item-level CVI (I-CVI) and scale-level CVI, universal agreement method (S-CVI/UA), was evaluated by five experts. Reliability was examined by internal consistency in 88 caregivers of 6 to 12-year-old students without the diagnosis of visual impairment, intellectual disability, and neurologic problems that influence movement, in a primary school in Bangkok, Thailand. Test-retest reliability was investigated three months apart in 85 caregivers. Inter-rater reliability was investigated in 20 pairs of both parents-teachers and parents-parents. Results: Both the I-CVI and S-CVI/UA of DCDQ-T were 1.0. The internal consistency showed a Cronbach’s alpha of 0.888. The intraclass correlation coefficient of test-retest reliability was 0.573. Inter-rater reliability between parents and teachers, and parents and parents were 0.199, and 0.149, respectively. Conclusion: DCDQ-T demonstrated an excellent CVI, good internal consistency, moderate test-retest reliability, and poor inter-rater reliability. Therefore, DCDQ-T could be a useful DCD screening tool for 6 to 12-year-old Thai children. However, a study on its repeatability and the degree of agreement among raters is further required.